Bleeding manifestation of post operative case in routine ENT surgery - a Caution for the young ENT Surgeons - Karim, R; Hossain, D; Martin, MA (KYAMC Journal, 2013)
DOI: http://dx.doi.org/10.3329/kyamcj.v1i2.13322 KYAMC Journal Vol.1(2) January 2011, 88-91